Hakikat Kuliah Kerja Lapangan dan Perubahan Masyarakat Kec. Dolok Kab. Padang Lawas Utara - Sawaluddin Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
This study aims to determine whether the work activities of the Field Work Lecture Program (KKL) of the Padangsidimpuan State Islamic Institute in response to the needs of the community, guide solutions to the problems faced by the Dolok District District community. North Padanglawas. By asking a question, how are the KKL students in the village? Is the KKL Student work program in accordance with community needs. This research is qualitative in the form of social studies. In collecting original data and accurate information done through interviews and observations. The collected data is then grouped, analyzed and then draws conclusions. Based on field interviews it can be seen that the placement of KKL students in Kec. Dolok is very much appreciated by the community. Students are intelligent, knowledgeable, intellectual, perceptive people who will certainly bring changes to village development. This statement can be seen from the work program of KKL students who are not only limited to making panplets, maintaining public facilities, painting mosques but also creating direct changes in the community such as education for children who have dropped out of school due to the weak economy, making aware of the use of land around the yard as a house additional financial resources, instilling awareness of the importance of maintaining health through counseling and establishing UKS, and various entrepreneurial activities such as turning sweet potatoes into various kinds of crackers, turning balakka into sweets.